Enhanced Performance of N-Polar AlGaN-Based Ultraviolet Light-Emitting Diodes With Lattice- Matched AlInGaN Insertion in n-AlGaN Layer - Hongchang Tao; Shengrui Xu; Yanrong Cao; Huake Su; Yuan Gao; Yachao Zhang; Jincheng Zhang; Yue Hao (IEEE Photonics Journal, 2023)
AlGaN-based ultraviolet-A light-emitting diodes (UVA LEDs) inevitably suffer from current crowding effects at high injection levels due to their lateral device structure, resulting in non-uniform light emission and device overheating. In N-polar UV LEDs, the problem is further exacerbated by increased hole injection efficiency, leading to current crowding and aggravated hole leakage, which limits the device performance. An n-AlGaN/AlInGaN/AlGaN structure is adopted in this study, through modulation of the Al and In compositions in the AlInGaN quaternary alloy, lattice matching and greater bandgap of AlInGaN to AlGaN template is designed. The numerical results prove that the n-AlGaN/AlInGaN/AlGaN structure can promote current spreading and thus mitigate hole leakage, resulting in the significantly enhanced performance of N-polar UVA LEDs. Furthermore, the use of lattice-matched AlInGaN layers in practical epitaxy is feasible, which can avoid the defect introduction resulting from the lattice mismatch.